Long-Term Reproductive and Gynecological Outcomes in Women with a History of Pelvic Inflammatory Disease - Nighat Aziz Wazir, Spogmai, Hira Hassan, Tahira Zeb, Umm E Kalsoom, Kalsoom Noor, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To assess the long-term reproductive and gynecological outcomes in women with a history of pelvic inflammatory disease (PID), with a particular focus on infertility, ectopic pregnancy, and chronic pelvic pain. It also explored the impact of comorbidities on these outcomes. Methodology: A retrospective study was conducted at the Department of Obstetrics and Gynecology, Hayatabad Medical Complex, Peshawar, from January 2023 to July 2023. A total of 150 patients with a history of PID were included, and they were divided into two groups: Group 1 (without major reproductive complications) and Group 2 (with infertility, ectopic pregnancy, or chronic pelvic pain). Data were analyzed using chi-square and t-tests to determine associations and significance, with a p-value of <0.05 considered statistically significant. Results: The study found that 100% of patients in Group 2 experienced infertility, 33.3% had ectopic pregnancies, and 20% had chronic pelvic pain. In contrast, Group 1 had no reproductive complications. Hypertension was significantly associated with infertility (p = 0.028), while the relationship between diabetes and infertility was not statistically significant (p = 0.130). The age distribution was similar between the groups (mean age of 32 years). The gender distribution showed 60% female and 40% male. Conclusion: The study confirmed that PID has significant long-term reproductive consequences, with infertility being the most prevalent outcome. Comorbidities, particularly hypertension, exacerbate these outcomes. Early diagnosis and effective treatment are crucial in mitigating the long-term effects of PID. Keywords: Pelvic Inflammatory Disease, Infertility, Ectopic Pregnancy, Chronic Pelvic Pain, Comorbidities.